POLITENESS STRATEGIES IN WEDNESDAY ADDAMS’ UTTERANCES: MAINTAINING SELF-IMAGE AND OTHERS’ AMIDST REJECTION - Syuhra, Marsha Aqillah Putri; Suhandoko, Suhandoko; Rochmah, Maulidya; Rosyidah, Nur (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
Communication is a form of bridge to convey thoughts between one individual and another. Every person must have their measure of being polite and harmonious according to who they are dealing with, including Wednesday Addams. This pragmatic research scrutinizes the politeness strategies employed by Wednesday Addams, the lead female protagonist in the Netflix series Wednesday. The character Wednesday Addams utilizes politeness strategies to maintain public and self-image during interactions while solving a murder case. Using descriptive qualitative methods, the researchers found that Wednesday frequently used bald on-record strategies with straightforward speech without being threatening. In contrast, off-record strategies were used less frequently. The researchers also observed that Wednesday used all the politeness strategies outlined by Brown and Levinson (1987). This study highlights the significance of politeness, not only for interpersonal relationships but also for achieving long-term goals, as demonstrated in the “Wednesday” series. However, further studies could provide additional perspectives and challenge the findings presented in this study.